Conceptualization of Wahdatul 'Ulum: A Philosophical Analysis of the Unity of Knowledge in the Islamic Scientific Tradition - Ahmad Nazir Siregar; Yusril Fahmi; Audia Zahara; Pusvita Ramadhani Nababan; Indra Utama Tanjung (ISNU Sumatera Utara, 2024)
The development of modern science has given birth to a fragmentation of science that separates religious science and general science, thus giving rise to an epistemological crisis in the Islamic educational tradition. This condition encourages the need to reconstruct a scientific paradigm that is able to integrate various disciplines in one complete philosophical framework. This study aims to analyze the conceptualization of Wahdatul 'Ulum as a paradigm of unity of knowledge in the Islamic scientific tradition, examine its philosophical foundation, its conceptual structure, and its relevance to the development of contemporary science. The research uses a qualitative approach with the library research method. Data were obtained from various primary and secondary literature related to Islamic epistemology, philosophy of science, and the thought of Muslim scholars, then analyzed using content analysis through a descriptive-analytical approach. The results of the study show that Wahdatul 'Ulum is an epistemological paradigm built on the unity of ontology, epistemology, and axiology based on the principle of monotheism. This paradigm views revelation, reason, senses, and intuition as complementary sources of knowledge and places all branches of science as one knowledge system oriented to the benefit of humans. Compared to various other models of science integration, Wahdatul 'Ulum not only offers curriculum integration, but also reconstructs a perspective on the essence of science. Thus, Wahdatul 'Ulum has philosophical relevance as a paradigm for the development of Islamic higher education, multidisciplinary research, and strengthening the ethical foundation of science in responding to epistemological crises in the era of globalization and technological development.